Pemanfaatan Penggunaan Quizizz Sebagai Latihan Soal Terhadap Hasil Belajar Siswa SMK Muhammadiyah 3 - Ramdani Putra; Qonaah Nuryan Arif; Fera Afriliya (Fakultas Teknik Universitas Cenderawasih, 2024)
The rapid development of science and technology can now be felt and influences human life. In the world of education, technology has a real positive impact on learning. Students can access more information and faster from various sources. Apart from that, there are many applications that teachers can use, such as PowerPoint, YouTube, or e-learning based systems as learning media. By utilizing technology, this research is descriptive research with a qualitative approach. This research contains a systematic explanation or presentation regarding the analysis of students' responses to the use of the Quizizz application as a learning alternative, there are 36 subjects from students at SMK Muhammdiyah 3 Pekanbaru. The aspects that you want to know are how learning activities are carried out using the Quizizz application, whether the Quizzizz application makes the learning atmosphere less boring, whether the application during learning using the usual method is a lot of dynamics felt by students. Of the 36 research respondents, some students said that learning went smoothly, but the majority of students said that learning was less effective, not conducive, boring, and that it was difficult to understand the material presented by the teacher. The problems experienced by these students occurred because of the guidance for students to always obey the rules and based on the results of the analysis found as study material, it can be concluded that the application of the Quizizz learning media is effective in improving the learning outcomes of elementary school students. Therefore, students need fun activities in learning, as well as building an active learning atmosphere so that they can understand the learning material better